Mud volcanism in the Gulf of Cadiz: results from the TTR-10 cruise - Pinheiro, LM
A new deep water mud volcano field (between 2000 and 3500 in water depth) was discovered in the deep South Portuguese margin, as well as several new mud volcanoes in the South Spanish and Western Moroccan margins of the Gulf of Cadiz, during the TTR-10 (Training Through Research, UNESCO/IOC) cruise, in July/August 2000. This work followed the discovery of a large mud volcano field in the Gulf of Cadiz, first investigated during the TTR-9 cruise [Gardner (2001) Geophys. Res. Lett. 28, 339-342; Kenyon et al. (2000) IOC, Technical series no. 56]. The discoveries were made based on a SEAMAP side-scan sonar mosaic and multibeam. bathymetry (SEABEAM) collected in the area by the Naval Research Laboratory (NRL), Washington, DC, USA, in 1992, kindly released for this purpose. Single-channel seismics, long-range side-scan sonar (OKEAN), TV-controlled grab, hull-mounted 3.5-kHz profiler and coring were used to investigate several seafloor features observed on the side-scan sonar imagery, in the South Iberia, Spanish and Moroccan margins of the Gulf of Cadiz, which were confirmed to be mud volcanoes. The typical structures related to fluid venting in the Gulf of Cadiz are essentially represented by conical mud volcanoes with diameters ranging from several tens of meters to 4 kin and heights that can reach 200 in. Some of these structures appear to be aligned along major conjugate NE-SW and NW-SE trending faults that can be identified on the side-scan sonar imagery. The new field discovered in the South Portuguese margin is the deepest in the Gulf of Cadiz area and includes three new mud volcanoes - Bonjardim, Olenin and Carlos Ribeiro - which seem to be quite active, with near-surface gas hydrate occurrence and a high saturation in H2S and hydrocarbon gases (mainly methane) in the mud breccia and overlying pelagic sediments. Gas hydrates were recovered from the Bonjardim mud volcano. An intensely gassified mud breccia, with one fragment of semi-consolidated claystone with a thin bituminous veneer at the surface, was recovered from the Carlos Ribeiro mud volcano. The fauna recovered consists mainly of pogonophoran worms belonging to several species and undetermined species of Foraminifera. Three new mud volcanoes were also discovered in the NW Moroccan margin: Rabat, Student and Jesus Baraza. These show a richer fauna that includes several species of molluscs, polychaetes, pogonophoran worms, crustaceans, echinoderms and some fragments of dead coral (Madrepora and Lophelia). Carbonate crusts were recovered from the Student mud volcano. The Ginsburg mud volcano, discovered during the previous TTR-9 cruise, was revisited and gas hydrates recovered once again. A new mud volcano was also discovered in the Spanish margin, Tasyo, where evidence was found of coral build-ups on the hard substratum of the mud volcanic edifice.